1995
DOI: 10.1108/eum0000000004116
|View full text |Cite
|
Sign up to set email alerts
|

Numerical prediction of fully developed turbulent swirling flows in an axially rotating pipe by means of a modified k—ε turbulence model

Abstract: A numerical study is performed to investigate turbulent flow characteristics in a pipe rotating around the axis. Emphasis is placed on the effect of pipe rotation on the friction coefficient and velocity distribution in the hydrodynamically, fully‐developed flow region. The k—ε turbulence model is modified by taking the swirling effect into account, in which the model function including the Richardson number is introduced to the ε equation. The governing boundary‐layer equations are discretized by means of a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…Consequently, heat transfer performance is intensified in the region between two orifices and in the vena contracta behind the rear orifice, as seen in Figure 5. Note that the asymptotic Nusselt number behind the rear orifice is the same value for three different rear orifice heights and approaches the numerical result (Torii, 1995) in the axially rotating pipe in the absence of the orifice (not shown). It is found that (i) the effect of pipe rotation on transfer performance in the region between two orifices and in the vena contracta behind the rear orifice is affected by the front and rear orifice heights and (ii) the heat transfer enhancement due to pipe rotation becomes larger when the dimensionless orifice height is 0.75.…”
Section: Governing Equations and Numerical Methodssupporting
confidence: 60%
See 1 more Smart Citation
“…Consequently, heat transfer performance is intensified in the region between two orifices and in the vena contracta behind the rear orifice, as seen in Figure 5. Note that the asymptotic Nusselt number behind the rear orifice is the same value for three different rear orifice heights and approaches the numerical result (Torii, 1995) in the axially rotating pipe in the absence of the orifice (not shown). It is found that (i) the effect of pipe rotation on transfer performance in the region between two orifices and in the vena contracta behind the rear orifice is affected by the front and rear orifice heights and (ii) the heat transfer enhancement due to pipe rotation becomes larger when the dimensionless orifice height is 0.75.…”
Section: Governing Equations and Numerical Methodssupporting
confidence: 60%
“…It is found that (i) the effect of pipe rotation on transfer performance in the region between two orifices and in the vena contracta behind the rear orifice is affected by the front and rear orifice heights and (ii) the heat transfer enhancement due to pipe rotation becomes larger when the dimensionless orifice height is 0.75. Prediction (Torii, 1995) Numerical simulation has been employed to investigate the thermal fluid flow in an axially rotating pipe with twin concentric orifices of different heights. Consideration is given to the influence of pipe rotation and orifice-shape on the formation of a vena contracta and the heattransfer performance behind the orifice.…”
Section: Governing Equations and Numerical Methodsmentioning
confidence: 99%
“…Standard eddy-viscosity models have shown largely poor results, with Torri et al 11 demonstrating an inability of the k − ε model to predict the effects of rotation unless corrections (using the Richardson correction 13 ) are included in the ε equation. However only limited results were presented so it is difficult to conclude the true performance of eddy-viscosity models.…”
Section: Rotating Pipementioning
confidence: 98%
“…We also consider the setup of Nishibori et al 7 where the rotating pipe section is extended to 200D. The previous experimental and computational studies [8][9][10][11] have shown two distinct regions in the rotating pipe section. In the first 20 − 40D an increase in the vorticity due to the rotation of the pipe causes a region of strong turbulence suppression 6,9 , where all components of the Reynolds stresses and turbulent dissipation rate decrease and the azimuthal velocity reaches a parabolic limit (in contrast to a laminar flow which would reaches a linear solid-body rotation profile).…”
Section: Rotating Pipementioning
confidence: 99%
“…Some researchers have suggested modifications to eddy viscosity models to account for strong rotation. For example, Dacles-Mariani et al [19] and Spalart and Shurr [20] have suggested modifications to the one equation eddy viscosity model given by Spalart and Allmaras [21] to sensitize the model to rotation and curvature while Torii and Yang [22] and Smirnov and Menter [23] suggested modifications to the two equation eddy viscosity models to achieve similar objectives.…”
Section: Introductionmentioning
confidence: 99%